El Edipo: una salida más allá de lo binario - Bermeo Sánchez, Ricardo Rafael; Figueroa Hurtado, Lionner Joe (Machala: Universidad Técnica de Machala, 2021)
The present investigation puts in context the most notable contributions of the psychoanalytic current, under the variables of "Oedipus Complex and Sexual Orientation". In order to interpret the link between the Oedipus Complex and the emergence of Sexual Orientations from the psychoanalytic perspective. For this, a bibliographic review and analysis of a case has been carried out later. In the first instance, Sigmund Freud's postulates state that a Sexual Orientation is hetero or different, it arises from the experience in the environment, emphasizing the phallic stage (between 3 and 6 years), being one of the stages most important subjects in psychosexual development. In its course, the infant naturally experiences situations that must solve and end the Oedipus Complex guided by an evolutionary framework. Otherwise, this becomes a negative Oedipus Complex, which would mark homosexual preferences in adult life. Subsequently, a review of heteronormativity and QUEER theories about sexual diversity in our context is established. To continue with the development of this research, the objective of the theme is to analyze the influence of the Oedipus Complex on Sexual Orientations. For this, a qualitative approach was used, the same one that allows to extract the most outstanding characteristics from a personal section. Such characteristics serve as a process to correlate the theoretical postulates with the events that are linked to their individual development, and that, as a product of this correlation, take for granted or otherwise the reality of both the classic postulates and the more recent postulates. Although from a professional perspective, as clinical psychologists, linked to psychoanalytic practice, it cannot be, nor is it intended to stagnate in a classic or rigid definition, but rather, as a proposal for optimal development in the ethical and professional development, it should be included constant updates on how sensitive people are to be dealt with. Furthermore, the subject focused on this thesis directly includes an approach subject to modifications or readjustments that allow the extraction of the most renewed knowledge, characteristics and complements of the basic theories to be complemented with the theoretical postulates without losing its essence. Simultaneously, as a sample it has been chosen to choose the non-probabilistic one, said sample is chosen based on the subjective judgment of the representatives of the thesis, avoiding making a random choice. At the same time, the “Life history” technique has been used as an instrument. This technique allows the use of all the necessary sources of bibliographic references, linked as a contribution to the development of the work without the need for the presence of the person. For the execution of the analysis of the case, categories have been extracted with the help of the MAXQDA software, to establish an objective analysis according to the personal history of the subject. It can be indicated that in their family environment there was a setback, which prevents the solution of the oedipal complex, which can be observed in adulthood. And as a conclusion we can say that the Oedipus Complex is nodal for the development of Sexual Orientation.
La presente investigación pone en contexto los aportes más notables de la corriente psicoanalítica, bajo las variables de Complejo de Edipo y la Orientación Sexual. Con la finalidad de interpretar el vínculo existente entre el Complejo de Edipo y el surgimiento de las Orientaciones Sexuales desde la perspectiva psicoanalítica. Para ello, se ha realizado una revisión bibliográfica y el análisis de un caso en lo posterior. En primera instancia, los postulados de Sigmund Freud manifiestan que una Orientación Sexual sea hetero o diferente, surge a partir de la vivencia en el medio, señalando con hincapié la etapa fálica (comprendida entre los 3 y 6 años), siendo una de las etapas más importantes de los sujetos en el desarrollo psicosexual. En su transcurso, de forma natural el infante experimenta situaciones que debe solucionar y dar fin al Complejo de Edipo guiado a partir de un cuadro evolutivo. De no ser así, este se convierte en un Complejo de Edipo negativo, el cual marcaría las preferencias homosexualizadas en la vida adulta. Posteriormente, se establece una revisión de la heteronormatividad y teorías QUEER sobre la diversidad sexual en nuestro contexto. Para continuar con el desarrollo de esta investigación, se responde al objetivo de la temática que es analizar la influencia del Complejo de Edipo en las Orientaciones Sexuales. Para ello, se utilizó un enfoque cualitativo, el mismo que permite extraer las características más resaltantes desde un apartado personal. Tales características, sirven como proceso para correlacionar los postulados teóricos con los acontecimientos que están ligados a su desarrollo individual, y que, como producto de esta correlación, dar por supuesto o por contrario la realidad tanto de los postulados clásicos como los postulados más recientes. Aunque desde una perspectiva profesional, como psicólogos clínicos, vinculados al ejercicio psicoanalítico, no se puede, ni se pretende estancar en una definición clásica o rígida, sino más bien, como propuesta a un óptimo desarrollo en el devenir ético y profesional, se debe incluir actualizaciones constantes en cuanto se deba tratar con la sensibilidad de las personas. Más aún, el tema enfocado en la presente tesis incluye de forma directa un abordaje sujeto a modificaciones o reajustes que permitan extraer los conocimientos, características y complementos más renovados de teorías bases para complementarse con los postulados teóricos sin perder la esencia del mismo. De manera simultánea, como muestra se ha optado por escoger la no-probabilística, dicha muestra es escogida en base al juicio subjetivo de los representantes de la tesis, evitando hacer una elección al azar. A su vez, se ha empleado como instrumento la técnica Historia de vida, mencionada técnica, permite hacer uso de todas las fuentes de referencias bibliográficas necesarias, vinculadas como aporte para el desarrollo del trabajo sin la necesidad de la presencia de la persona. Para la ejecución del análisis del caso, se han extraído categorías con la ayuda del software MAXQDA, para establecer un análisis objetivo de acuerdo a la historia personal del sujeto. Se puede indicar que en su ambiente familiar existió una contrariedad, que impide la solución del complejo edípico, mismo que se puede observar en la adultez. Y como conclusión podemos decir, que el Complejo de Edipo es nodal para el desarrollo de la Orientación Sexual.
Keywords: EDIPO; PSICOANALISIS; ORIENTACION SEXUAL; HETERONORMATIVIDAD